An Exploratory Study to Detect Ménière’s Disease in Conventional MRI Scans Using Radiomics - van den Burg, E. L.; van Hoof, M.; Postma, A. A.; Janssen, A. M. L.; Stokroos, R. J.; Kingma, H.; van de Berg, R. (Frontiers in Neurology, 2016)
Abstract Objective The purpose of this exploratory study was to investigate whether a quantitative image analysis of the labyrinth in conventional MRI scans using a radiomics approach showed differences between patients with Ménière’s disease and the control group. Materials and methods In this retrospective study, MRI scans of the affected labyrinths of 24 patients with Ménière’s disease were compared to the MRI scans of labyrinths of 29 patients with an idiopathic asymmetrical sensorineural hearing loss. The 1,5T and 3T MRI scans had been previously made in a clinical setting between 2008 and 2015. 3D Slicer 4.4 was used to extract several substructures of the labyrinth. A quantitative analysis of the normalized radiomic image features was performed in Mathematica 10. The image features of the two groups were statistically compared. Results For numerous image features, there was a statistically significant difference (p-value <0.05) between the Ménière’s disease group and the control group. The statistically significant differences in image features were localized in all substructures of the labyrinth: 43 in the anterior semicircular canal, 10 in the vestibule, 22 in the cochlea, 12 in the posterior semicircular canal, 24 in the horizontal semicircular canal, 11 in the common crus and 44 in the volume containing the reuniting duct. Furthermore, some figures contain vertical or horizontal bands (three or more statistically significant image features in the same image feature). Several bands were seen: 9 bands in the anterior semicircular canal, 1 band in the vestibule, 3 bands in the cochlea, 0 bands in the posterior semicircular canal, 5 bands in the horizontal semicircular canal, 3 bands in the common crus and 10 bands in the volume containing the reuniting duct. Conclusion In this exploratory study, several differences were found in image features between the Ménière’s disease group and the control group by using a quantitative radiomics approach on high resolution T2 weighted MRI scans of the labyrinth. Further research should be aimed at validating these results and translating them in a potential clinical diagnostic method to detect Ménière’s disease in MRI scans.